A Philosophical and Ethical Concept of Environmental Democracy: New political organization in the face of climate change - Quesada Rodríguez, Francisco (2025)
This article presents the current discussion about environmental democracy as a political and philosophical theory in a state of creation to confront the ecological and climate crisis. To understand the origins and development of this theory, a review is made of the state-of-the-art of environmental and ecological democracy, considering the theories in English and French, which have not yet entered into critical dialogue. Finally, a philosophical and ethical concept of environmental democracy is presented to offer deliberative, participatory, and ethical responses to the humanitarian and planetary situation resulting from climate change.